Pilkada di Bali: Kecakapan Melaksanakan Hak Pilih di tengah Beragamnya Regulasi Umur Dewasa - Dewi, Ni Komang Ratih Kumala; Pratiwi, Agustina Ni Made Ayu Darma (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: This research was conducted with the aim of analyzing competencies in exercising the right to vote amidst various adult age regulations in regional head elections (pemilihan kepala daerah or Pilkada) in Bali. Research methods: The method used in this research is the category/type of normative research. Results and discussion: The problem of competencies in terms of authority to act in Pilkada Bali cannot be resolved simply using this principle. This is due to the emergence of new rules that provide authority to act which is at odds with competency requirements. In several provisions regarding the minimum age limit for the right to carry out legal actions, the authority to act is of course related to competence. Even though every person has rights from birth, they are not necessarily competent to take legal action. Implications: Clear regulations are needed to determine the age limit for a person to be able to carry out all legal actions. If we are based on new laws such as the child protection law, then we must be consistent in regulating a person's adult age, lest there are other regulations that regulate different adult ages.